Comparing the degradation of acetochlor to RhB using BiOBr under visible light: A significantly different rate-catalyst dose relationship - Yi-Zhu, Peng; Wan-Hong, Ma; Man-Ke, Jia; Xiao-Rong, Zhao; Johnson, David M.; Ying-Ping, Huang (Applied catalysis. B, Environmental, 2016)
[Display omitted] •Increasing BiOBr significantly accelerate photodegradation of non-polar acetochlor.•The rate-dose relationship of acetochlor/BiOBr and RhB/BiOBr is different.•The adsorption capacity of acetochlor decreased as the BiOBr dose increased.•More BiOBr will adsorb more polar substrates (like RhB). In this study, a weakly polar pesticide acetochlor in water was tried to degrade by BiOBr catalysts under visible light irradiation. Its degradation reaction rate increased exponentially with increasing catalyst dosage, which was significantly different from conventional photocatalytic patterns established for polar or water-soluble pollutants. Thus, the rate-dosage relationship of BiOBr/acetochlor was compared to that of BiOBr/Rhodamine B (RhB) (a typical strong polar dye pollutant in water) at different BiOBr dosages. The degradation rate of RhB increased with the BiOBr dosage and then plateaued due to more catalyst particles blocking the light into the inner solution, which is a typical behavior for heterogeneous photocatalysis of polar organic compounds in aqueous solution. While acetochlor behaved differently, its degradation rate increased exponentially with the BiOBr dosage, and no plateau was observed even up to 9.0g/L BiOBr dosage. This special rate-dose relationship for weakly polar acetochlor was correlated with a unique adsorption property of BiOBr to acetochlor in water solution. There was a re-distribution effect that always exclude excessive acetochlor adsorbed on BiOBr surface regardless either substrates or BiOBr overdose. This finally resulted in every BiOBr particle having enough adsorption sites available for dissolved dioxygen to function thereby accelerate the degradation of weakly polar organic compounds in water.